2009
DOI: 10.2471/blt.07.047423
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to physical and sexual violence and adverse health behaviours in African children: results from the Global School-based Student Health Survey

Abstract: Objective To examine associations between exposure to physical violence (PV) or sexual violence (SV) and adverse health behaviours among a sample of children in five African countries. Methods In a cross-sectional analysis of data from Namibia, Swaziland, Uganda, Zambia and Zimbabwe -countries that participated in the Global School-based Student Health Survey in 2003 or 2004 -we compared the relative frequency of several adverse health behaviours among children (primarily students 13-15 years of age) who did a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
97
4
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 7 publications
7
97
4
6
Order By: Relevance
“…Only three peer-reviewed studies have assessed the mental health needs of children in Namibia and these studies do not provide population-based data. 22,23,24 This is despite the fact that a national representative study to assess the living conditions of people with disabilities reported that almost half the respondents stated that the onset of their disability took place before the age of five. 25 Data from neighbouring South Africa, a country which shares many social and historical similarities with Namibia, shows that there is a high level of unmet need in South Africa.…”
Section: Introductionmentioning
confidence: 62%
“…Only three peer-reviewed studies have assessed the mental health needs of children in Namibia and these studies do not provide population-based data. 22,23,24 This is despite the fact that a national representative study to assess the living conditions of people with disabilities reported that almost half the respondents stated that the onset of their disability took place before the age of five. 25 Data from neighbouring South Africa, a country which shares many social and historical similarities with Namibia, shows that there is a high level of unmet need in South Africa.…”
Section: Introductionmentioning
confidence: 62%
“…Data on sexual risk factors were not collected, and we may have underestimated sexual abuse as a reason for being HIV-infected, as participants and their guardians may have been reluctant to divulge this. However, although we do not discount the high rates of sexual abuse reported from African countries, 31 at the population level penetrative forced sex during childhood occurs at a much lower frequency than does exposure to HIV at birth and in infancy in this region, with the possible exception of South Africa. 32 The thematic analysis performed may be subject to interpretivism (i.e., constructs created by the investigators) in that the views of the participants were constructed by the study investigators, and thus verbatim quotes have been provided to illustrate the main themes.…”
Section: Discussionmentioning
confidence: 99%
“…In the WHO Multi-country study on women's health and domestic violence against women, 3-24% of women reported that their first sexual experience was forced, and that for a majority of respondents this occurred during adolescence (9).A Nigerian study found that 45% of females and 32% of males aged 12-21 years reported having had forced sexual intercourse (10). More recently, a study of over 20 000 schoolchildren aged 13-15 years in Namibia, Swaziland, Uganda, Zambia and Zimbabwe found that 23% reported having experienced sexual violence (physically forced to have sexual intercourse) at some point in their live (11). In other study 37% of the victim girls were found to be 16-20 yrs of age.…”
Section: Discussionmentioning
confidence: 99%